Use of Gen-Probe AccuProbe Group B streptococcus test to detect group B streptococci in broth cultures of vaginal-anorectal specimens from pregnant women: comparison with traditional culture method. - Bourbeau, P P (1997)
Detection of vaginal-anorectal colonization with group B streptococci (GBS) is critical to the prevention of neonatal GBS disease. The recommended method for the detection of GBS is culture of the distal vagina and anorectum in a selective broth medium followed by subculture to solid media and identification of GBS on the solid media. The purpose of this study was to compare this standard culture method with the detection of GBS directly from an enrichment broth by utilizing the Gen-Probe AccuProbe Group B Streptococcus Culture Identification Test (GPGB). A total of 502 specimens were tested in this study. Both culture and the GPGB detected 90 of 95 positive specimens (sensitivity, 94.7%). There were two false-positive GPGB results (specificity, 99.5%). An analysis of 100 consecutive specimens was performed to compare the costs associated with the use of a primary tryptic soy agar plate with 5% sheep blood (BAP) and a 3-ml tube of Todd-Hewitt broth supplemented with 10 micrograms of nalidixic acid per ml and 15 micrograms of colistin per ml (LIM broth) with subculture to another BAP and the costs associated with the GPGB. Our estimated costs were $3.68 for a negative culture including 7.0 min of labor, $5.41 for a positive culture including 8.9 min of labor, and $5.16 for the GPGB including 3.6 min of labor (based upon a test run of 10 specimens and two controls and a cost of $70.00 for a 20-test GPGB kit). Accessioning and reporting of results are not included in these costs. In conclusion, we found that the GPGB was equivalent in sensitivity to our standard culture method. While overall costs were somewhat higher for the GPGB, the GPGB has lower labor costs and offers the potential for incremental savings with higher test volumes and computer interface capability.